Magneto-Erythrocyte Membrane Vesicles’ Superior T2 MRI Contrast Agents to Magneto-Liposomes - Nina Kostevšek; Patricija Miklavc; Matic Kisovec; Marjetka Podobnik; Wafa Al-Jamal; Igor Serša (Magnetochemistry, 2021)
Despite their high potential, most of the clinically approved iron oxide (IO)-based contrast agents for magnetic resonance imaging (MRI) have been withdrawn from the market either due to safety issues or lack of sales. To address this challenge, erythrocyte membranes have been used to prepare IO-based T2 contrast agents with superior MRI properties and higher safety margin. A simple formulation procedure has been proposed, and the nanostructures’ morphology and physicochemical properties have been evaluated. We compared their performance in terms of contrast ability in MRI to the more clinically established magneto-liposomes and non-encapsulated nanoparticles (NPs). The encapsulation of 5-nm iron oxide nanoparticles (IO NPs) in the liposomes and erythrocyte membrane vesicles (EMVs) led to a significant improvement in their r2 relaxivity. r2 values increased to r2 = 188 ± 2 mM−1s−1 for magneto-liposomes and r2 = 269 ± 3 mM−1s−1 for magneto-erythrocyte membranes, compared to “free” IO NPs with (r2 = 12 ± 1 mM−1 s−1), measured at a 9.4 T MRI scanner. The superiority of magneto-erythrocyte membranes in terms of MRI contrast efficacy is clearly shown on T2-weighted MR images. Our study revealed the hemocompatibility of the developed contrast agents in the MRI-relevant concentration range.